Solve for m 26=m/6+5

Math
26=m6+5
Rewrite the equation as m6+5=26.
m6+5=26
Move all terms not containing m to the right side of the equation.
Tap for more steps…
Subtract 5 from both sides of the equation.
m6=26-5
Subtract 5 from 26.
m6=21
m6=21
Multiply both sides of the equation by 6.
6⋅m6=6⋅21
Simplify both sides of the equation.
Tap for more steps…
Cancel the common factor of 6.
Tap for more steps…
Cancel the common factor.
6⋅m6=6⋅21
Rewrite the expression.
m=6⋅21
m=6⋅21
Multiply 6 by 21.
m=126
m=126
Solve for m 26=m/6+5

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top